The dual effect of vagus nerve stimulation in pediatric patients with drug-resistant epilepsy: Is there more than seizure control? - Mohamed Ashraf Mahmoud; Omnia El Rashidi; George Halim; Mohamed Amgad Elkholy; Osama Aglan; Abdel Rahman El Sabbagh; Ahmed Kamel Basha; Hussein Hamdi; Ahmed M. El Sayed; Dina Amin Saleh; R.H. Shatla; Walid Abdel Ghany (Epilepsy & Behavior Reports, 2024)
This is a retrospective and comparative pilot study to investigate the role of vagus nerve stimulation (VNS) in improving cognitive functions in the pediatric age group with drug resistant epilepsy (DRE). It was conducted from January 2018 to February 2023. Children between the ages of 4 and 18 years were divided into two groups, the “VNS group” and the “best medical treatment (BMT) group”. Follow up period was 12 months. Demographic, clinical, etiological and investigational data were recorded. Cognitive assessment using the Modified Mini-Mental State Examination for children (MMSE) was recorded at baseline and 12 months later for each group. 76.4 % of patients were classified as epilepsy secondary to cerebral palsy. 75 % of patients showed ≥ 50 % seizure frequency reduction among the VNS group as compared to 12.5 % in the BMT group. None of both groups achieved seizure freedom. At 12 months, both BMT and VNS groups showed statistically significantly improved overall cognitive score from baseline records (p = 0.027) and (p = 0.012), respectively, with a significantly higher improvement in VNS group. Also, statistical sub-analysis of cognitive subscales in cerebral palsy patients in both groups was conducted and revealed a significant improvement (p = 0.02) in the VNS group. We concluded that there is a potential role of VNS in improving cognitive functions which was shown by using a cost-effective screening tool. A significant effect was observed specially in cerebral palsy patients. This is very beneficial in limited-resources countries since VNS has good safety profile, high seizure control, and added value to cognitive functions.